Surface passivation of InAs avalanche photodiodes for low-noise infrared imaging - Ker P.J.; Marshall A.R.J.; Tan C.H.; David J.P.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Avalanche photodiodes; Characterization; Diodes; Infrared imaging; Leakage currents; Nitrides; Photodiodes; Photonics; Silica; Silicon nitride; Thermography (imaging); B-staged bisbenzocyclobutene; Current-voltage characterization; InAs; Low noise; Surface leakage currents; Surface passivation; Passivation